Ванильный Новый год: [сказка] / Наталья Карпова ; художник Мария Коротаева - Карпова Наталья Владимировна (Нигма, 2019)
Экземпляры: ф.10 (20211202) / Инвентарный номер: 46219 / Цена: / Авт.знак: К 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44